On the asymptotic behavior of \(L_p\) extremal polynomials
Let \(β \) denote a positive Szeg? measure on the unit circle \(Γ \) and \(δ _z_k \) denote an anatomic measure (\(δ \) Dirac) centered on the point \(z_k.\) We study, for all \(p>0,\) the asymptotic behavior of \(L_p\) extremal polynomials with respect to a measure of the type \[ α =β +_k=1^∞ A_kδ _z_k , \] where \({ z_k} _k=1^∞ \) is an infinite collection of points outside \(Γ \)., number=2, journal=Rev. Anal. Numér. Théor. Approx., author=Laskri, Yamina and Benzine, Rachid, year=2005, month=Aug., pages=125–134